A STUDY OF SPEECH ACTS IN “CALL ME BY YOUR NAME” MOVIE: Speech Act, Call Me by Your Name Movie - Sherlie Vitriana; Novi Sriwulandari (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2023)
The part of pragmatics that is learned by the students is speech act. Speechact is using utterances to perform some actions, in any occasions speech actemerges in uttterances like in the movie, talk show, novel and many others. Thisstudy intend to analyze speech act used by one of the main characters in “Call me by Your Name Movie movie” movie script. In the analysis is to investigate what acts emerge behind the utterances and the impacts for the hearer after the utterances is stated. The statements of research problem are: 1) what are the illocutionary actsused by Elio and oliver as one of the main characters in Frozen movie script? The Elio and Oliver as one of the main characters in “Call me by Your Name Movie movie” script, and the next purpose is to describe illocutionary act used by Elio and Oliver as one of the main characters in “Call me by Your Name Movie movie” movie script. Research method of this research: the research design of this research is library research with qualitative approach, the data of this research is the utterances of Elio and Oliver as one of the main characters in “Call me by Your Name Movie movie” movie script and the data sourceis “Call me by Your Name Movie movie” movie script. To analyse the data the researcher did some steps:Watching the “Call me by Your Name Movie movie” movie story well,Read the movie script classified the data into the types of illocutionary act of Searle' classification used by Elio and Oliver as one of the main characters in the “Call me by Your Name”. The result of the data analysis showed that there were five types ofillocutionary act base on searle’s classifications, they were: 1) 18 utterances ofrepresentative were like Well, he was sprightly, 2) 12 utterances of directives werelike Elio, go back to sleep, 3) 5 utterances of commisives were like We arenever closing them again, 4) 16 utterances of expressive were like It was anaccident. I’m sorry, Oliver and 5) 4 utterances of declaratives were like Hi, I’mElio and I like warm hugs. Futhermore, the next result were perlocutionary act ofthe data had been classified into illocutionary acts base on searle’e classificationfound 43 effects were like May I talk to you, please. Alone.